HUBUNGAN ANTARA SIKAP TERHADAP KEBIASAAN SARAPAN PAGI DENGAN TINGKAT BERAT BADAN PADA SISWA SD “X” - Endang Fourianalistyawati; Tiara Fitri Ramadhani (Universitas Bunda Mulia, 2015)
Excess or lack of weight has a negative risk in children. Cross-sectional study in 3227 parents who have 5-6 years old children showed that children who have excess or lack of weight can have quality of life disorders related to physical health problems. The results of research conducted by Tapper also found that attitudes towards breakfast habits become behavioral predictions breakfast. But it turns out in fact that it is not always proven. Therefore, researchers wanted to see whether attitudes towards breakfast habits have a correlation with the level of a person's weight or not. This research used a correlation type. Participants in this study were 127 students of SD